Thrift-growth nexus for the regional comprehensive economic partnership countries - Çolak, Olcay; Bölükbaşı, Ömer Faruk (Universitas Islam Indonesia, 2025)
Purpose — This study examines the relationship between savings and economic growth, accounting for the mediating role of financial development across the selected Regional Comprehensive Economic Partnership (RCEP) countries. Methods — Using a panel data set spanning 1986 to 2022, the long-run interaction among the variables is investigated with panel cointegration methods that account for cross-sectional dependence. Moreover, the associated long-run elasticities were estimated using the augmented mean group estimation method. The causal nexus was examined for each country in the sample. Findings — In addition to the presence of a long-run relationship, the findings revealed that both thrifts and growth have a positive influence on each other in the long run. In addition, bidirectional causality tends to exist between thrifts and growth. Implication — Since the findings disclose the validity of two mainstream macroeconomic views, policymakers should rely on developing economic policies aiming at fostering thrift and economic growth, which may include support of institutional quality and financial deepening in those economies. Originality — The originality and added value of the study stem from the development of a new perspective, particularly in the examination of causal relationships. Furthermore, this is one of the primary efforts focused on the RCEP bloc, which has significant potential in terms of trade, finance, thrifts, and economic size in the contemporary world economy.